Analisis Kontribusi Sektor Perhubungan terhadap Pendapatan Asli Daerah di Kabupaten Aceh Tengah - Ravika Ramadayani; Irwan Nasution; Armansyah Matondang (Universitas Medan Area, 2018)
The function of regional autonomy is to regulate and manage government affairs in the region, the implementation of regional autonomy has an important influence for each region to be more creative in utilizing existing economic resources in the region for the successful implementation of development in the region. In this case the Central Aceh District Government seeks to explore the potential of funds that can increase Regional Original Revenue, one of which is from the Transportation sector. The problem that was formulated was